(untitled) (Patrimônio e Memória, 2014)
The paper discusses the uses and functions of photography in the nineteenth century, in particular the practice of collecting photography in this century, notably in Brazil. It is important to define collecting as a universal social practice, and the collection as a representation of its collector. This paper also aims to discuss the impact of the creation of photographic processes on the habit of collecting, as well as the uses and functions of photography in the nineteenth century in the practice of collecting photographs. There is a discussion of the relevance of the Imperial Family as disseminator and collector of photography, and of the characteristics of photography collecting by the elite in nineteenth century Brazil.